PERAN PROJECT MANAGER DAN ACCOUNT EXECUTIVE DALAM PROGRAM GOVERNMENT PUBLIC RELATIONS UNTUK MENINGKATKAN PARTISIPASI MASYARAKAT MELALUI LAPOR SEMAR SOLUSI AWP - Shara Meilisa Ardini; Nurist Surayya Ulfa (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
Lapor Semar Solusi AWP is a digital public complaint service under the Department of Communication and Informatics (DISKOMINFO) of Semarang City, formerly known as Sapa Mbak Ita. The rebranding on April 8, 2025 led to decreased awareness, trust, and public participation toward the new identity. This study aims to evaluate the role of Government Public Relations in improving these aspects through the campaign “Cipta Seni Bahana Aspirasi #NgadudiLaporSemar.” The Project Manager is responsible for planning and monitoring the campaign, while the Account Executive handles coordination, stakeholder relations, and content management. The results show increased public awareness, improved trust, and a rise in new users. These findings indicate that structured Government Public Relations strategies are effective in enhancing the use of digital public complaint services.